PENURUNAN JUMLAH SANTRI BARU DI PONDOK PESANTREN MODERN BANTEN TAHUN 2026 (Analisis studi kasus enam Pesantren Modern di Banten) - Maman Lukman (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
The Islamic boarding school, the oldest Islamic educational institution in Indonesia, has a very strategic role, many great contributions to building the civilization of the people and the nation. Islamic Boarding School Law No. 18 of 2019. Have duties and functions; Education, da'wah. and Community Empowerment. The purpose of the Islamic Boarding School is to form superior individuals who understand and practice religious teachings, have faith, are pious, have noble character, are knowledgeable, independent, Mandatory Elements of the Islamic Boarding School; Kiyai, a student who lives in a residential area, studies the yellow book or Dirasah Islamiah with the Muallimin Education Pattern. Principles of Islamic Boarding School Administration; The One Godhead, nationality, independence, empowerment, benefits, multiculturalism, professionalism, accountability, sustainability, legal certainty. The recognition of the State of Islamic Boarding Schools is recognized as part of the national education system. In recent years, various studies have shown a tendency to decrease the interest of students/parents/the community to enter various Islamic boarding schools, especially Modern Islamic Boarding Schools nationally, the number of students has plummeted dramatically, the Ministry of Religion's EMIS data decreases: Academic year 2025/2026 odd semester: 2,315,046 students in Islamic boarding schools Academic year 2026/2027 odd semester: 1,264,936 students. Down 45.36% in 1 year. This happens in Modern Islamic Boarding Schools in Banten? Banten has 6,776 Islamic boarding schools, the 4th most in Indonesia, which is very logical if it is also affected. As a result of the author's interviews with six leaders of the Modern Islamic Boarding School in Banten during July 2026, there has been a decrease in new students at the Modern Islamic Boarding School in Banten by 35%-65%, The author uses a research method through interviews and analysis of various scientific studies, there are several elements of the cause; 1. Negative sentiments from several immoral events that go viral, becoming a stigma of negative image; 2. Competition with Integrated Islamic Schools, Tahfidz and Boarding and Non-Dormitory-based Technology-based schools. It also competes with fellow Modern Islamic boarding schools which are not much different; 3. Economic factors of the family, country and the international world, and 4. The shift in the interest of parents and the "Z" generation who are pragmatic, comfortable, easy, and loose on rules, is very dependent on gaget/cellphone. The solution; Every pesantren leader all feels grateful for the existing situation, but must continue to make efforts; Islamic boarding schools must improve, digital strategy efforts are active in uploading positive works and activities through mainstream media and social media; Improvement of management governance, upgrading Islamic boarding school human resources, masterplan of professional infrastructure facilities and modernization of the alignment of stakeholders, the community, especially the state are present in the middle of Islamic Boarding Schools. In conclusion, this is not easy to do, but if you want to survive, you must continue to experience changes and improvements, it is hoped that the results will be good.